Bericht und Gedanken über die United Nations Conference on Desertification (UNCOD) in Nairobi/Kenia vom 29. August 1077 bis 9. September 1977 - Mensching, Horst (ERDKUNDE, 1978)
The present paper is a report on the United Nations Conference on Desertification (UNCOD) in Nairobi/Kenya, which took place from August 29 to September 9, 1977. Special stress is being laid on the task of Geography to participate both in working out the natural and social basis and in carrying out case studies in the arid, semiarid and subhumid climatic zones of the developing countries. The most significant UNCOD background papers are being discussed and analysed.